Conservation agricultural practices promoted arbuscular mycorrhizal fungal colonization and glomalin content on sandy clay loam of southern India - Knight Nthebere; Tata Ram Prakash; Padmaja Bhimireddy; Latha P. Chandran; Jayasree Gudapati; Meena Admala; Kavuru Prasad (Heliyon)
Arbuscular mycorrhizal Fungi (AMF) are essential in agriculture and are often inter-linked with glomalin-related soil protein (GRSP) production which supports binding of aggregates, enhanced SOC and biological attributes. However, conservation agricultural practices in agroecosystem may have significant impact on AMF diversity, GRSP and soil quality-related parameters (SQRPs). This current experiment was implemented to gauge AMF conization percentage (AMF-CP), GSRP and significant changes on critical SQRPs, and to investigate the linkages between AMF-CP, GRSP and SQRPs as influenced by synergistic tillage and weed management in CA. Contrasting tillage practices (Main plots) included the T1:Conventional tillage with cotton- Conventional tillage with maize-fallow i.e., No Sesbania rostrata (Farmers’ practice), T2:Conventional tillage with cotton- Zero tillage with maize- Zero tillage with Sesbania rostrata and T3: Zero tillage with cotton + Sesbania rostrata residues- Zero tillage with maize + Cotton residues- Zero tillage with Sesbania rostrata + Maize stubbles. Weed management tactics (Sub plots) were W1: Chemical weed control, W2: Herbicide rotation, W3: Integrated weed management and W4: Single hand-weeded control. The roots and soil samples were collected at 60 DAS of maize. Analysis of examined parameters was done duly following standard protocols. The observed results indicated that 22.50 % of AMF-CP, 16.50 % of EE-GRSP and 12.08 % of T-GRSP was significantly higher in conservation tillage compared to T1 (Farmers practice). SQRPs followed similar trend in the case of tillage. Significantly higher SMBC and β-galactosidase (β-GaA) was exhibited by W4 and W3. A highly significant positive correlation of AMF-CP and T-GRSP pool with SOC (r = 0.951∗∗ and 0.756∗∗), SMBC (r = 0.872∗∗ and r = 0.761∗∗), β-GaA (r = 0.916∗∗ and r = 0.832∗∗) and WSA1–2mm (r = 0.888∗∗ and 0.882∗∗), respectively was also observed. Generally, AMF-CP and GRSP, and SQRPs correlated positively and significantly. The following parameters; T-GRSP, SOC, WSA1–2mm, SMBC and β-GaA were selected as potential indicators to gauge the soil quality based on calculated principal component analysis (PCA). In general, the examined parameters in the study are highly supported by zero-till + crop residues, and can be considered indicators for monitoring agroecosystem.